The Effect of Endorphin Massage on Reducing Anxiety Levels During the First Stage of Labor - Didin Prasetya Cahyaningsih; Rifzul Maulina (KHD Production, 2026)
Anxiety in mothers entering the latent phase of the first stage of labor can arise due to various factors, including psychological conditions, lack of family support, fear of the birthing process, limited information, and physical complaints experienced during labor. One non-pharmacological approach that has the potential to help reduce anxiety is endorphin massage, a massage technique believed to stimulate the release of endorphins, which are natural stress reducers. This study aims to assess the effectiveness of endorphin massage in reducing anxiety levels in pregnant women. The research design used a quantitative descriptive method with a one-group pretest–posttest approach. A total of 25 mothers in the first stage of labor at TPMB Diah Ulul in Probolinggo City were included in the sample. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. Univariate analysis was used to describe the distribution of results, while differences in anxiety scores were tested using the t-test. The results showed a statistically significant decrease in anxiety after endorphin massage (t = 19.5; p < 0.001), with the average HARS score decreasing from 29.9 to 13.9. These findings indicate that endorphin massage is an effective non-pharmacological intervention and can be recommended as a supportive measure to help reduce anxiety in laboring mothers, thereby potentially improving comfort and the quality of the birthing experience.